Gender Analysis of Educational Support Programs for OVC in Uganda and Tanzania: Are they Helping Girls in Secondary School? - Brooks, Mohamad; Bryant, Malcolm; Shann, Mary; Bukuluki, Paul; Muhangi, Denis; Lugalla, Joe; Kwesigabo, Gideon (Vulnerable Children and Youth Studies, 2014)
Gender plays an important role in education as most traditional societies give preference to boys over girls when it comes to educational opportunity. Increasing access to education for girls is important to the health and well-being of the individual, their future children, families, and communities. The objective of this paper is to understand the gender differences in educational outcomes for orphans and vulnerable children (OVC) attending secondary schools in Uganda and Tanzania. The study employed a four-year, retrospective record review utilizing both qualitative and quantitative methodologies. A total of 5738 student records were collected as part of the study. Students were grouped as “ever supported” OVC (receiving educational support from either a block grant or scholarship program during their secondary school education), “never supported OVC” (OVC students who did not receive any educational support), and “nonOVC students” (students identified by the school as neither orphaned nor vulnerable). Results of the study indicate that investment in secondary school education for OVC in Uganda and Tanzania can make a difference in educational outcomes, both for boys and girls. Although there was no gender difference in absenteeism or dropout rate among students those who received educational support, stark differences were found in secondary school Year IV national examination pass rates with girls significantly less likely to pass compared to boys. The disparity in secondary school learning achievement between male and female students is of concern and warrants further investigation.
Keywords: OVC; orphan; vulnerable children; education; gender; evaluation; Uganda; Tanzania